2006
DOI: 10.1002/bit.20810
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and survival changes in Saccharomyces cerevisiae during suspension culture

Abstract: This study explores the connection between changes in gene expression and the genes that determine strain survival during suspension culture, using the model eukaryotic organism, Saccharomyces cerevisiae. The Saccharomyces cerevisiae homozygous diploid deletion pool (HDDP), and the BY4743 parental strain were grown for 18 h in a rotating wall vessel (RWV), a suspension culture device optimized to minimize the delivered shear. In addition to the reduced shear conditions, the RWVs were also placed in a static po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…Of these, 513 were up-regulated and 384 were down-regulated); Previous microarray analyses of yeast growing in LSMMG also showed expression changes, although the total number of genes involved was much less than we observed [1,2]. In a related study, Johanson et al [2] identified 140 differentially expressed genes in which a significant number of genes are involved in catalytic activity. Few are the same as genes identified in our experiment.…”
Section: Resultscontrasting
confidence: 43%
See 2 more Smart Citations
“…Of these, 513 were up-regulated and 384 were down-regulated); Previous microarray analyses of yeast growing in LSMMG also showed expression changes, although the total number of genes involved was much less than we observed [1,2]. In a related study, Johanson et al [2] identified 140 differentially expressed genes in which a significant number of genes are involved in catalytic activity. Few are the same as genes identified in our experiment.…”
Section: Resultscontrasting
confidence: 43%
“…Cellular responses to the environment are mediated by phenotypic changes ultimately driven by alterations in gene expression, some of which resemble environmental stress responses [1,2]. Microorganisms such as yeast serve as powerful eukaryotic models for experimentally investigating the effects of microgravity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such bioreactor named as high-aspect-ratio vessel (HARV, Synthecon) [3] was used in this study. The HARV employed for cell suspension culture and tissue growth permits cell growth in suspension and minimizes the fluid shear levels encountered by cells [1], [4]. When the cell culture vessel rotates, microbial cells do not settle down but revolve around a horizontal axis and continuously fall through the fluid at 1×g terminal velocity condition, which lead to 1∼2×10 −2 gravity environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anchorage-dependent cells, the gene expression of the budding yeast, Saccharomyces cerevisiae, is affected by shear stress. [23] It is therefore desirable to take shear damage into account when designing and fabricating microchannel or bioreactor. [7] This Communication addresses a method of forming bottleshaped, hollow polymeric microstructures inside a microfluidic channel for potential shear-protecting cell reservoirs.…”
mentioning
confidence: 99%